간호 ․ 간병통합서비스병동 간호사의 업무위임 가이드라인 개발. - 이 여 진; 임 해 나; 김 지 미; 송 정희 (Journal of Korean Academy of Nursing Administration, 2024)
Purpose: The aim was to develop guidelines for delegating nursing tasks among nurses in integrated nursing care wards. Methods: This was a methodological approach. Literature reviews were conducted on delegation policies and practices for nurses in Korea and other countries to explore the area of nursing delegation. Focus group interviews were performed with nurses to identify the strength and weakness of the delegation of nursing tasks in clinical practice, and qualitative content analysis was conducted based on the interview. Ten areas and 115 items were derived through these steps, and their validity was confirmed using the Delphi technique. Results: The delegation guidelines of nursing tasks consisted of nine domains, 21 sub-categories, and 101 items, including Nurses and nursing assistants' duties, the necessity of delegation, definition of terms, scope of delegation, considerations for delegation, procedure, characteristics, and principles of delegation, and educational content for delegation. Conclusion: These guidelines can help nurses to make decisions about delegating nursing tasks according to the delegation procedure. Education on the delegation of nursing tasks is necessary for both nurses and nursing assistants. The guidelines developed in this study can serve as a standard for delegating nursing tasks to ensure patient safety.